The potential of using Satellite Remote Sensing for identifying the impact of climate change on existing reinforced concrete (RC) structures - Stylianou, Stella; Filippou, Christiana; Tantele, Elia; Votsis, Renos; Kyriakides, Nicholas (My University, 2023)
Concrete is a widely used construction material worldwide due to its high durability over time. Despite the long-term performance of concrete, there are still failures in reinforced concrete (RC) buildings due to the deterioration of concrete caused by environmental and weather conditions. Also, climate change accelerates the deterioration processes in RC structures and affects their safety and serviceability. Therefore, there is an urgent socio-economic need for optimum maintenance and repair of existing RC structures according to climate changes for achieving acceptable levels of structural safety. To achieve this, the science of satellite remote sensing is essential for quantifying and providing up-to-date information on the climate changes occurring in the atmosphere, land, and oceans on a global scale. This paper presents the influence of climate change on existing RC structures. At the same time, this paper highlights the potential of using satellite remote sensing for identifying the impact of climate change on existing RC structures in order to accurately assess the performance of existing building stock and, then to propose efficient and optimum maintenance and repairing strategies toward a resilient society.